Menakar Pengaruh Perubahan Sistem Pemilihan Legislatif 2024 dari Melalui Mekanisme Judicial Review di Mahkamah Konstitusi - Moch Rasyid Gumilar (CV Rewang Rencang, 2023)
Indonesia has undergone several electoral system changes historically since 1955. General elections serve as a crucial mechanism to demonstrate the sovereignty of the people in a democratic state. In regard to electoral system changes through judicial review, it involves an examination of legislative regulations conducted by a judicial institution. The Constitutional Court (MK) must consider whether such changes fall under the category of open legal policy or not